Effect of composition and configuration on hindered diffusion of residue fractions through polycarbonate membranes. Issue 4 (25th July 2012) - Chen, Zhentao; Gao, Jinsen; Zhao, Suoqi; Xu, Zhiming; Xu, Chunming
<x xml:space="preserve">Abstract</x> Diffusion behavior of narrow fractions of three residues and subfractions of a residue through four polycarbonate membranes was investigated using a diaphragm cell at 308 K. The results show that the diffusivities of fractions with similar molecular weight behaved differently. Comparisons among SAR subfractions (saturates, aromatics, and resins) of the same fraction show that saturates has the largest diffusion coefficient, followed by aromatics, and then resins. The diffusion coefficients of fractions fall among that of their subfractions. The regular variation of diffusivity along with the properties for fractions with similar molecular weight is an indication of the difference in their diffusivities resulting from the difference in their compositions and structures. Hindrance factors of the subfractions through membranes with small pores have a similar variation trend as their diffusion coefficients. The hindrance factors of the feedstocks in 50 and 80 nm pore size membranes are mostly larger than 0.90, but the values in 15 nm membranes range from 0.55 to 0.81. The study not only indicates that the diffusional limitations are significant in pores with the typical hydrotreating catalyst size but composition and configuration have an effect on the hindered diffusion of residue molecules. © 2012 American Institute of Chemical Engineers AIChE J, 59: 1369–1377, 2013